The Beneficial Role of Filipendula ulmaria Extract in Prevention of Prodepressant Effect and Cognitive Impairment Induced by Nanoparticles of Calcium Phosphates in Rats. (12th February 2021) - Arsenijevic, Natalija; Selakovic, Dragica; Katanic Stankovic, Jelena S.; Mihailovic, Vladimir; Mitrovic, Slobodanka; Milenkovic, Jovana; Milanovic, Pavle; Vasovic, Miroslav; Markovic, Snezana D.; Zivanovic, Marko; Grujic, Jelena; Jovicic, Nemanja; et al.
Abstract : Mineral components of dental composites are used in many medical and dental applications, including preventive, restorative, and regenerative dentistry. To evaluate the behavioural alterations induced by nanosized particles of novel dental composites, by means of depressive level and cognitive functions, experimental groups of rats were chronically administered with nanosized hydroxyapatite (HA), tricalcium phosphate (TCP), and amorphous calcium phosphate (ACP) with or without simultaneous application of Filipendula ulmaria L. (FU) methanolic extract. The significant prodepressant action was observed in groups solely treated with HA and ACP. Besides, prolonged treatment with ACP also resulted in a significant decline in cognitive functions estimated in the novel object recognition test. The adverse impact of calcium phosphates on estimated behavioural functions was accompanied by increased oxidative damage and apoptotic markers in the prefrontal cortex, as well as diminished specific neurotrophin (BDNF) and gabaergic expression. The results of our investigation showed that simultaneous antioxidant supplementation with FU extract prevented calcium phosphate-induced behavioural disturbances, as well as prooxidative and apoptotic actions, with the simultaneous restoration of BDNF and GABA-A receptors in the prefrontal cortex. These findings suggest that FU may be useful in the prevention of prodepressant impact and cognitive decline as early as the manifestation of calcium phosphate-induced neurotoxicity.